Therapeutic potential of ginseng leaf extract in inhibiting mast cell-mediated allergic inflammation and atopic dermatitis-like skin inflammation in DNCB-treated mice - Oh, Jung-Mi; Yoon, HyunHo; Joo, Jae-Yeol; Im, Wan-Taek; Chun, Sungkun (Frontiers in Pharmacology, 2024)
Ginseng leaves are known to contain high concentrations of bioactive compounds, such as ginsenosides, and have potential as a treatment for various conditions, including fungal infections, cancer, obesity, oxidative stress, and age-related diseases. This study assessed the impact of ginseng leaf extract (GLE) on mast cell-mediated allergic inflammation and atopic dermatitis (AD) in DNCB-treated mice. GLE reduced skin thickness and lymph node nodules and suppressed the expression and secretion of histamine and pro-inflammatory cytokines. It also significantly lowered the production of inflammatory response mediators including ROS, leukotriene C4 (LTC4), prostaglandin E2 (PGE2), cyclooxygenase-2 (COX-2), and inducible nitric oxide synthase (iNOS). GLE inhibited the phosphorylation of MAPKs (ERK, P38, JNK) and the activation of NF-κB, which are both linked to inflammatory cytokine expression. We demonstrated that GLE's inhibitory effect on mast cell-mediated allergic inflammation is due to the blockade of the NF-κB and inflammasome pathways. Our findings suggest that GLE can be an effective therapeutic agent for mast-cell mediated and allergic inflammatory conditions.